"Reinventing the wheel" as an emerging business model innovation paradigm. Issue 5 (8th May 2017) - Ghezzi, Antonio
Abstract : Purpose: This study aims to discuss how business model innovation from both incumbents and startups growingly may stem from past products, services, and approaches reinvented. This results in what is labeled the "Reinventing the Wheel (RTW)" innovation paradigm, where the future is seen through the lenses of the past. Design/methodology/approach: This study is based on historical analysis of common business model innovation patterns found in a longitudinal sample of both incumbent companies and startups in the time frame 2008-2016. Findings: The RTW paradigm unlocks business model innovation through: the reinvention of past resources and competencies; the use of digital technologies; and the centrality given to customer experience and customer journey. The resulting RTW cycle is made of five steps to follow in the attempt to make the most out of this paradigm: survey, learn, disclose, exploit, and reinvent. Practical implications: Entrepreneurs and managers are presented with the key elements, steps, and implications of an emerging business model innovation paradigm to possibly apply in their incumbent or startup context. Originality/value: This study presents an original approach to look at business model innovation, in a way that is complementary to alternative practices like the blue ocean strategy, big-bang disruption, and lean startup.